Low-Temperature Thermal Conductivity of the Two-Phase Superconductor CeRh2As2 - Onishi, Seita; Stockert, Ulrike; Khim, Seunghyun; Banda, Jacintha; Brando, Manuel; Hassinger, Elena (Frontiers in Electronic Materials, 2022)
CeRh2As2 is a rare unconventional superconductor (Tc = 0.26 K) characterized by two adjacent superconducting phases for a magnetic field H ∥ c-axis of the tetragonal crystal structure. Antiferromagnetic order, quadrupole-density-wave order (T0 = 0.4 K) and the proximity of this material to a quantum-critical point have also been reported: The coexistence of these phenomena with superconductivity is currently under discussion. Here, we present thermal conductivity and electrical resistivity measurements on a single crystal of CeRh2As2 between 60 mK and 200 K and in magnetic fields (H ∥ c) up to 8 T. Extrapolation of our normal-state data to zero temperature validates the Wiedemann-Franz law within the error bars. The T dependence of the thermal conductivity κ(T) shows a pronounced drop below Tc which is also field dependent and thus interpreted as the signature of superconductivity. However, the large residual resistivity and the lack of sharp anomalies in κ(T) at the expected transition temperatures clearly indicate that samples of much higher purity are required to gain more information about the superconducting gap structure.